Hypertension: Dominant Risk Factor on Stroke Occurence Analytical Observational Study in Sultan Agung Islamic Hospital Semarang during January 1, 2012 - August 31, 2013 - Saputri, Desia Laila Dian; Rosdiana, Ika; Lestari, Endang (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2015)
Introduction: Stroke ranks as the first cause of disabilities and the third cause of death in the world. Many factors associated with stroke. Objective: this study aimed at evaluating the factors associated with stroke. Study Design: This study was an analytical observational study using cross sectional design. Samples were obtained from medical records of 263 patients who were admitted in neurology’s ward of Sultan agung Islamic hospital during 1 January 2012-31 August 2013. Samples categorized in 2 groups: 97 hemorrhagic’s stroke patients and 166 non hemorrhagic’s stroke patients with simple random sampling technique. This study were conducted by analyzing 5 variables such as gender, age, hypertension, diabetes mellitus and total cholesterol levels. Results: Logistic regression test using SPSS showed that hypertension was the most dominant factor associated with stroke (p=0.001; PR=1.707; CI=1.249–2.433). Conclusion: Hypertension was the most dominant risk factor for stroke.